Dilatation and curettage versus manual vacuum aspiration for first trimester clandestine abortions - Nkwabong, Elie; Fomulu, Joseph Nelson (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Unintended pregnancy rate is rising worldwide and most of these pregnancies end by clandestine abortion. This study aimed at comparing complications of clandestine abortions done with Manual Vacuum Aspiration (MVA) to those of clandestine abortions done with Dilatation and Curettage (D&C). Methods: This retrospective descriptive study was carried out in the Yaoundé University Teaching Hospital (Cameroon) from March 1st to August 31st, 2012. Abortions carried out with MVA or D&C were recruited. Main variables studied were abortionist, method used, complications presented and hospital stay. Data were analyzed using SPSS 18.0. Analyses included the t test and the Fisher exact test. The level of significance was P <0.05. Results: Main abortionists were nurses and general practitioners. Compared to MVA, women in the D&C group had more uterine perforations (P=0.004), severe anemia (OR 1.5, 95%CI 0.5-4.3), prolonged hospital stay (P=0.018) and maternal death (one case). D&C done by nurses carried more risk of severe complications (OR 3.6, 95%CI 0.2-53.8). Conclusions: MVA constitutes a safer method than D&C. However, abortionists should receive adequate training before using MVA.